MENTAL HEALTH OF SPECIALISTS AND EMOTIONAL STATE OF INFANTS WHO ARE IN INSTITUTIONAL CARE - Juodraitis, Adolfas; Radzevičienė, Liuda; Strakšienė, Diana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
An article tries to reveal presumptive relationships of mental health of special educators and emotional stage of infants. In this context we discuss mental health of teachers (reasons and signs of it) and emotional reactions of infants. In specific educational environment mental health of teachers is an important factor of successful pedagogical process and infant development, as well. Pedagogue in Infant home acts as a creator of the stimulating environment for child’s space of development. The analysis of expression of emotional status of infants let us draw a conclusion, that optimal psychological health of caregivers impresses emotional condition of deprived infants. The boys are more influenced by psychological condition of caregivers then girls.